(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The opportunity for the public to give their opinion and follow the development of legislation is not only a practice of full-fledged democracy and good governance, but also an opportunity for the public administration to obtain information, knowledge and analysis that it did not have access to. The aim of this study is to analyse the impact of digitisation on representation of interests and public involvement in the development of legislation in Latvia. The analysis of quantitative and qualitative data explored 4,943 legislative advancement processes in the Single Portal for Development and Harmonisation of Draft Legal Acts (TAP portal) between 2018 and 2024. Digitization of the final phase of the development of legal acts, i.e. public discussion and coordination in Latvia allows to assess: 1) how actively society is involved; 2) who does it – simple citizens or professional organizations; 3) whether digitization has increased public involvement; 4) whether public involvement significantly slows down decision-making. The results show that the infrastructure of the TAP Portal has successfully promoted the involvement of organized interest groups in the process of harmonization of legal acts, mainly in the form of legal entities and associations. The participation of private individuals is small. The original objectives of the TAP Portal have been exceeded as it has been used by more than 600 different types of actors. At the same time, the hypothesis that organised groups significantly slow down decision-making processes was not confirmed; the length of decisions is more influenced by the political agenda and the nature of the legislation. The study confirms the role of the Single Portal for Development and Harmonisation of Draft Legal Acts as an important platform in promoting transparency and efficiency in the development of legal acts. The authors recommend continuing to promote the use of this portal among interest groups, as this would enhance both transparency of the process and balanced representation of interests in the legislative process.